Categories of return among Spanish refugees and other migrants 1950s-1990s: Hypotheses and early observations - Alicia Pozo-Gutierrez; Scott Soo (Les Cahiers de Framespa)
Whether for ideological or material circumstances, migration was a defining experience for twentieth-century Spain. While studies have focused on the experiences, issues and challenges of migrants in the various host countries, there is a lacuna in our understanding of return migration to Spain. This article stems from a pilot project on the return migration to Spain of exiles and other migrants to from the 1950s to the 1990s and seeks to understand the motivations, experiences and memories of return. The aims of this article are: firstly to explore return migration as a plural phenomenon, secondly to call into question the view that the desire but inability to return resulted in a paralysing form of nostalgia; and thirdly to shift attention away from a tendency of public discourses to eulogise the memory of ‘integration’ by focusing on a less publicised phase of the migration cycle.